Motivation of foreign students to study at preparatory departments as a social psychological problem - Fisenko, Olga (2021)
The article contains a social psychological research of foreign students’ motivation to study at Russian universities. The author reviews the psychological concepts of studying motivation. The author analyses foreign students’ motives of building communication skills, as well as the role motivation plays in educational activities.